Peran Digitalisasi Perpajakan dan Literasi Digital terhadap Kepatuhan Pajak UMKM di Era Ekonomi Digital - depita sinaga; Christina Hotmatondini Turnip; Krisna Sarinauli Lumban Siantar; Putri Angelita BR Purba; Munzir Phonna (Jurnal Ekonomi dan Bisnis Digital, 2026)
Indonesia's transition toward a digital tax administration system has transformed the way tax services are delivered, particularly through e-Filing, e-Billing, e-Faktur, and the Coretax Administration System. Although MSMEs account for 60.51% of the national GDP and serve as a major pillar of economic growth, their level of tax compliance continues to present challenges. The success of digital tax initiatives is closely linked to the ability of taxpayers to utilize digital technologies effectively. Accordingly, this article investigates the contribution of tax digitalization and digital literacy to improving MSME tax compliance in the digital era. The study employs a Systematic Literature Review (SLR) method guided by the PRISMA 2021 framework and analyzes 17 journal articles published from 2019 to 2025, sourced from Google Scholar and Scopus. The review reveals that digital tax services simplify administrative procedures and encourage higher levels of formal compliance. Nevertheless, the impact of these innovations is influenced by the digital literacy level of MSME participants. Several obstacles remain, including inadequate digital skills, disparities in technology access, and resistance to behavioral change. The article proposes digital education initiatives as an essential complement to MSME taxation policies.